2021
DOI: 10.21608/aimj.2021.73939.1463
|View full text |Cite
|
Sign up to set email alerts
|

Effect of moderate iron deficiency anemia during pregnancy on maternal and fetal outcome.

Abstract: Users have the right to read, download, copy, distribute, print, search, or link to the full texts of articles under the following conditions: Creative Commons Attribution-Share Alike 4.0 International Public License (CC BY-SA 4.0).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Twenty-two of these studies defined anemia using the WHO-conformant threshold of <11 g/dl (Table 1), 9,10,12,14,16,3046 the other 24 studies fell into the Lower or Unspecified Threshold groups and were analyzed separately (Table 2). 11,13,15,4767…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-two of these studies defined anemia using the WHO-conformant threshold of <11 g/dl (Table 1), 9,10,12,14,16,3046 the other 24 studies fell into the Lower or Unspecified Threshold groups and were analyzed separately (Table 2). 11,13,15,4767…”
Section: Resultsmentioning
confidence: 99%
“…Gestational anemia has a negative impact on fetal weight, evidenced by an increased rate of LBW [41,49,60]. Numerous studies have demonstrated a higher incidence of LBW and ELBW among adolescents than adults [15,61,62].…”
Section: Discussionmentioning
confidence: 99%